IDE DAN PRAKSIS NEO-NASIONALISME DALAM MENGHADAPI TANTANGAN GLOBALISASI - Hendropriyono, A. M. (Jurnal Filsafat "WISDOM", 2008)
AbstractNowadays, Indonesia national history is moving to universalism and will experience the historical paradox process, namely, the movement unified as a result of science and technology development that are able to protect. Men will be flowed to grouping in their own national community. It happens for human being claim justice and freedom. In the one hand, Capitalists as chief of globalization, nowadays, carry Neo-Liberalism as a thesis; in the other hand, there is Universal-Islam that carries Radicalism or terrorism as anti-thesis. Although they use a same language,reciprocally, they can not understand each other. The two languages, as if, come from two contradictory cultures, therefore, undoubtedly, they create the clash of civilization. The paradoxical and conflict phenomena will reduce if community in nation-state success in consolidate base on their consciousness, that the synthesis of social-dialectic in this age is a new and fresh national life, as the raising of Neo-Nationalism in the Nation-States in all over the world.Keywords: Neo-Nationalism, Globalization and Nation-States